A computational framework for fluid–structure interaction with applications on stability evaluation of breakwater under combined tsunami–earthquake activity. (25th June 2022) - Huang, Shuai; Liu, Chuanzheng
Abstract: In this article, an improved impervious solid boundary condition of the coupled method called smooth particle hydrodynamics and discrete element method (SPH‐DEM) is proposed, which prevents the fluid particles from penetrating solid boundary under earthquake action. And an improved transmitting boundary condition of SPH‐DEM is designed in order to conquer the reflection of seismic waves on the boundary. Meanwhile, the effective stress method is proposed to be applied to the SPH‐DEM for simulating seabed liquefaction. Based on these, a new computational framework for the SPH‐DEM is put forward. Dynamic triaxial test of seabed soil samples indicate that our proposed computational framework can well reproduce the seismic liquefaction process of the seabed soil. Moreover, our proposed computational framework is used to numerically reproduce the failure mechanisms of a breakwater built in liquefied seabed under combined tsunami–earthquake activity and meantime the centrifuge test is carried out. And the experimental results demonstrate the effectiveness of our proposed computational framework, in which numerical results of it are consistent with results of the centrifuge test.